(Dis)agreement, polarity, and focus: Answering negative polar questions in Italian. Issue 1 (9th January 2018) - Servidio, Emilio; Bocci, Giuliano; Bianchi, Valentina
Abstract : Among languages that employ specialized particles for answering polar questions, two major groups are known: Positive-Negative (P-N) and Agreement-Disagreement (A-D). English and Italian are examples of the former group, Japanese an example of the latter. It has occasionally been remarked in the literature that at least in some P-N languages a narrow focus in a negative polar question affects the choice of responding particles: namely, the answering pattern shifts to A-D. In the present contribution, this claim is thoroughly tested experimentally with two forced choice experiments that investigate the choice of responding particles in answers to Italian negative polar questions both with and without narrow foci. Our results bring clear support to the claim of the exceptional answering pattern to negative polar questions with narrow foci. Two candidate accounts are presented, in accord with the two main current lines of research on responding particles: an ellipsis account and an anaphoric account. In both cases, we will argue that a crucial role is played by the interaction of the narrow focus with sentential negation in the questions.